Corpos em movimento a partir do olhar de Pina Bausch – construindo modos de dançar - Araújo, Pedro Simon Gonçalves (2015)
This work is the result of a research project that was conducted by the Graduate Program in Art and Visual Culture, master´s level, in FAV-UFG, and aimed to immerse in the dance theater practice, through paths traced by the German choreographer Pina Bausch, who was a guide in the development os this research and helped me to answer personal questions, which the principal aim was to discover how our histories, memories and feelings are represented in body. This research started with a watchful eye in the dance history, as well as in the creative process of Pina Bausch to be able to understand the method of creating images by the body and her representations through cinema. Her unique movie “The Lament of the Empress” had an important function in structuring the Project, since questions that were shared with two other dancers in an immersive practive came from it, and led to the creation of a documentary that dialogues with the videodance and brings through interviews, essays and movements research a sample of a body-affective experience also shared with students from the Federal Institute of Goiás. In a play between theories and reports I sought the different perceptions of the body and dance, crisscrossing authors of visual culture, movement researchers, theories of representation, documentary, which merged with the reports of the meetings with dancers, ballet lessons, contemporary dance and some workshops. The aim was to achieve tangible answers that unravel the pathways of the body and image to find my dance through my body.